Keys to curriculum mapping : strategies and tools to make it work - Udelhofen, Susan (Corwin Press, 2005)
Packed with templates, flowcharts, tips & trouble-shooting for curriculum mapping, this user friendly resource is grounded in the author's consulting work with schools, conference presentations & research on effective schools.